An AR-Guided System for Fast Image-Based Modeling of Indoor Scenes - Andersen, Daniel; Popescu, Voicu (2018 IEEE Conference on Virtual Reality and 3D User Interfaces (VR), 2018)
We present a system that enables a novice user to acquire a large indoor scene in minutes as a collection of images that are sufficient for five degrees-of-freedom virtual navigation by image morphing. The user walks through the scene wearing an augmented reality head-mounted display (AR HMD) enhanced with a panoramic video camera. The AR HMD visualizes a 2D grid partitioning of a dynamically generated floor plan, which guides the user to acquire a panorama from each grid cell. The panoramas are registered offline using both AR HMD tracking data and structure-from - motion tools. Feature correspondences are established between neighboring panoramas. The resulting panoramas and correspondences support interactive rendering via image morphing with any view direction and from any viewpoint on the acquisition plane.